Sea clutter scattering, the K distribution and radar performance - Ward, Keith D. (Institution of Engineering and Technology, 2013)
The book covers five parts. Part one belongs to sea clutter properties. Part two discusses the mathematics of the K-distribution. Part three covers the radar detection and Part four deals with physical modelling of radar.
Keywords: Distribution (Probability theory); Electromagnetic waves -- Scattering.; Radar -- Interference -- Mathematical models.; elektronické knihy; electronic books